STUDY OF OPERATION OF ARC STEEL FURNACE WITH CONOID BAY FLUSHING OF STEEL - M. A. Murikov; D. N. Andrianov; V. N. Prohorenko; V. M. Nosovets; I. V. Grinkevich (Литьë и металлургия)
The construction of the arc steel-furnace bay, the application of which allows to increase the speed of flush outflow, to provide reduction of the slag carry-over with metal, is offered.